KETIDAKTEPATAN KODE DIAGNOSA KASUS NEOPLASMA MENGGUNAKAN ICD-10 DI RS SANTA ELISABETH MEDAN - Pomarida Simbolon (Program Studi Perekam Medis & Informasi Kesehatan, 2021)
Medical record is a file that contains notes and documents about patient identity, examination, treatment, actions and other services that have been provided to patients and documented in the disease classification coding system. One of the disease codifications is neoplasm, which is a grouping of diseases into a group of similar disease code numbers according to ICD-10. Neoplasm cases are one of the most common diagnoses at Santa Elisabeth Hospital, Medan. The aim of the study was to determine the diagnosis coding for neoplasms at Santa Elisabeth Hospital, Medan. Descriptive research design. Data collection is done by observation. The number of samples used were 34 documents with simple random sampling technique. The research was carried out in July 2021. Data analysis was carried out descriptively. The results obtained that the completeness of the morphological code for the diagnosis of neoplasms in the inpatient medical record documents carried out at the Santa Elisabeth Hospital, namely 28 documents (82.4%) were complete, and 4 documents (17.6%) were incomplete. The accuracy of the topographic code for the diagnosis of neoplasms was complete with 31 documents (73.5%) and 3 documents incomplete (14.7%). The factor that causes the inaccuracy of coding is that it is difficult for the coding officer to read the doctor's writing, so it is necessary to train coding officers.